Time-dependent resonant inelastic X-ray xcattering of pyrazine at the nitrogen K-edge: a quantum dynamics approach - Freibert, Antonia; Mendive-Tapia, David; Huse, Nils; Vendrell, Oriol (Journal of chemical theory and computation, 2024)
We calculate resonant inelastic X-ray scattering spectra of pyrazine at the nitrogen K-edge in the time domain including wavepacket dynamics in both the valence and core-excited state manifolds. Upon resonant excitation, we observe ultrafast non-adiabatic population transfer between core-excited states within the core-hole lifetime, leading to molecular symmetry distortions. Importantly, our time-domain approach inherently contains the ability to manipulate the dynamics of this process by detuning the excitation energy, which effectively shortens the scattering duration. We also explore the impact of pulsed incident X-ray radiation, which provides a foundation for state-of-the-art time-resolved experiments with coherent pulsed light sources.